The effect of transient fetal bradycardia and other heart rate changes during and after external cephalic version on perinatal outcomes. (February 2020) - Hruban, Lukas; Janků, Petr; Jordanova, Kristyna; Huptych, Michal; Jouzova, Anna; Gerychova, Romana; Ventruba, Pavel
Abstract: Objectives: To evaluate the effect of transient fetal bradycardia and other heart rate changes during and after external cephalic version (ECV) on perinatal outcomes. To determine factors associated with a higher risk of occurrence of transient fetal bradycardia during and after ECV. Study design: Prospective study in 286 women after the 36th week of gestation with a fetus in breech presentation who have undergone an ECV attempt. The study analyses the incidence of transient fetal bradycardia during and immediately after ECV, the time interval to complete adjustment of fetal bradycardia, the factors associated with the occurrence of transient fetal bradycardia, cardiotocography (CTG) changes after ECV and perinatal outcomes. All the data were statistically analyzed. Results: The ECV was successful in 51 % (146/286). Transient fetal bradycardia occurred during and after ECV in 81 cases (28.3 %). A successful version was a factor significantly associated with fetal bradycardia (54; 37.0 % versus 27; 19.3 %; p < 0.01). Clinically significant hypotension of the mother was accompanied by transient fetal bradycardia in 12 cases (4.2 %). After the successful ECV there was no significant difference in the percentage of vaginal deliveries between subgroups with and without transient fetal bradycardia (85.2 % versus 83.7 %; p = 1.00). Nor in occurrence of acute fetal distress during labor (18.5 % versus 15.6 %; p = 0.65). In cases of a successful ECV transient CTG changes after ECV had no effect on the incidence of acute fetal distress during labor (23.5 % versus 15.7 %; p = 0.49). Conclusions: Transient fetal bradycardia and other heart rate changes during and immediately after ECV was not associated with a higher incidence of acute fetal distress during labor and did not affect perinatal outcomes. Higher occurrence of transient bradycardia after ECV was associated only with successful ECV. Transient hypotension of the mother as one of the causes of transient fetal bradycardia during ECV should be considered.